Pengaruh Pelatihan Kerja Dan Pengembangan Karir Terhadap Kinerja Pegawai Pada Badan Pengawasan Keuangan Dan Pembangunan (BPKP) Perwakilan Provinsi Sulawesi Selatan - Yastin Resu (Intellektika : Jurnal Ilmiah Mahasiswa, 2023)
The purpose of this research is to find out how professional training and career development impact employee performance. The South Sulawesi Province Representative Financial and Development Supervisory Agency (BPKP) is the subject of this inspection. This research uses primary data; Samples were obtained using random sampling and data analysis was carried out using multiple linear analysis. The samples collected were 40 employees. The survey results were tested for reliability and validity using multiple linear regression analysis and hypothesis testing, t test and F test. Positive and significant results were obtained through analysis of the relationship between employee performance variables (Y) and training variables (X1), with a significance level of (0.004 <0.05). Positive and significant results were obtained using the career development variable (X2) with a significance threshold of t (0.000 <0.05). However, based on the results of simultaneous tests with a significance level of t < a (0.000 – <0.05), the variables are employee performance (Y) and professional training (X1) and career development (X2) as well as conveying positive and meaningful results to others.